(untitled) (diségno, 2019)
On the borderline between the disciplines of drawing and landscape design there is a terrain vague with interesting intersections which, in my opinion, should be examined. This is an issue that for me, at least, is more sensitive, today, now that I deal more with these problems in my dear old niche of a studio, that is, the artisan workshop I started out in. I am pleased to mention these intersections on this occasion, in which you give me the honor of introducing such a highly qualified assembly of authors. (read more)